A road to trust - Labonne, Julien (Policy research working paper, 2008)
"The authors explore the relationship between transaction costs and generalized trust. Using panel data from 2,100 households in 135 rural communities of the Philippines, the paper shows that where transaction costs are reduced (proxied by road construction), there is an increase in generalized trust. Consistent with the argument that generalized trust is built through repeated interactions, the authors find that the individuals most likely to engage in exchange exhibit an increase in trust after road construction. These results suggest that, rather than being an input to economic growth, trust might be a product of reduced transaction costs (which also favors growth). "--World Bank web site